Pertanggungjawaban Hukum Terhadap Maraknya Kasus Judi Online di Kalangan Remaja Menurut Perspektif Hukum Pidana - Maulana Ibrahim, Indah Puja Claudia Damanik, Tengku Salsabila, Reh Bungana Beru Perangin-Angin, (Mediation : Journal of Law, 2023)
The rise of online gambling among the public, especially teenagers, is a problem that is difficult to eradicate in Indonesia. Therefore, online gambling is classified as a crime (cyber crime) because of its criminal activity. This study aims to see how legal accountability for online gambling cases that occur among adolescents from a criminal law perspective. The research method carried out is to use the normative juridical approach method, namely the legal literature method by reviewing document studies based on secondary data, be it through laws, legal theories, legal concepts, legal principles and expert opinions, then the data is presented descriptively in words. This study found that criminal law regulations regarding online gambling have not been fully accommodated, so in handling cases like this, of course, the government must also take part in providing socialization about law enforcement and punishment for online gambling perpetrators.